A Facile Synthesis of Green‐Blue Carbon Dots from Artocarpus lakoocha Seeds and Their Application for the Detection of Iron (III) in Biological Fluids and Cellular Imaging. Issue 42 (13th November 2019) - Yadav, Pradeep Kumar; Singh, Vikas Kumar; Kumar, Chandan; Chandra, Subhash; Jit, Satyabrata; Singh, Sushil Kumar; Talat, Mahe; Hasan, Syed Hadi
Abstract: Herein, a facile, green and eco‐friendly approach has been applied for the synthesis of fluorescent green‐blue carbon dots (GB‐CDs) through the one‐pot hydrothermal treatment of Artocarpus lakoocha seeds for the first time and entirely characterized via a variety of instrumental techniques like fluorescent spectroscopy, Transmission Electron Microscopy (TEM), X‐Ray Photoelectron Spectra (XPS), X‐Ray diffraction (XRD) and Fourier Transform Infra‐red (FTIR) analysis. The as‐prepared GB‐CDs displayed high fluorescent quantum yield (QY) up to 38.5% and high photostability based on which GB‐CDs were successfully applied as a sensitive nanoprobe for the detection of Fe 3+ ion. The sensing of Fe 3+ shows a linear range from 2 to 6 μM and the limit of detection was found to be 0.62 μM. The sensing of Fe 3+ was further investigated in the bona fide sample like river water and human blood serum. In addition, to explore the potential application, MTT assay was carried out on SH‐SY5Y neuroblastoma cells. The results showed negligible cytotoxicity as well as high cell viability, which revealed that GB‐CDs could be utilized as a fluorescent probe in living cells. Abstract : A natural source, Artocarpous lakoocha have been used for the synthesis of carbon dots through one‐step hydrothermal method. The carbon dots exhibited green‐blue fluorescence under ultra‐violet light (365 nm). Furthermore, the carbon dots were used for the selective and sensitive detection of iron (III) ion. Addition to this, the sensing of iron (III) ion was also performed in SH‐SY5Y neuroblastoma cells.